1990
DOI: 10.1002/1097-0142(19900415)65:8<1816::aid-cncr2820650825>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of intramural metastasis in patients with esophageal carcinoma

Abstract: Clinicopathologic data on 201 patients who underwent surgical resection of esophageal squamous cell carcinoma, with or without intramural metastasis (IM), were analyzed to determine the significance of IM for patient prognosis and survival. In 24 (11.9%) patients IM was observed. There was one (1.4%) in 74 cases in Stage 0, I, or II, and 23 (18.1%) in 127 cases in Stage III or IV, based on the new pTNM classification. There was a statistically significant Cox-Mantel test difference in the percentage survival c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1

Year Published

1992
1992
2014
2014

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 7 publications
1
50
1
Order By: Relevance
“…Compared with primary lesions without IM in esophageal squamous cell carcinoma, the clinicopathological features of primary lesions with IM are reported to include advanced stage grouping, a higher rate of lymph node metastasis (79-99 %), and a higher rate of capillary invasion (76-100 %) [1][2][3]9], features that correspond to the results of this study in gastric cancer. Distant metastasis was detected in 37.9 % of IM in this study, whereas the reported rate of IM is 29.2 % in esophageal cancer [2].…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…Compared with primary lesions without IM in esophageal squamous cell carcinoma, the clinicopathological features of primary lesions with IM are reported to include advanced stage grouping, a higher rate of lymph node metastasis (79-99 %), and a higher rate of capillary invasion (76-100 %) [1][2][3]9], features that correspond to the results of this study in gastric cancer. Distant metastasis was detected in 37.9 % of IM in this study, whereas the reported rate of IM is 29.2 % in esophageal cancer [2].…”
Section: Discussionsupporting
confidence: 69%
“…Distant metastasis was detected in 37.9 % of IM in this study, whereas the reported rate of IM is 29.2 % in esophageal cancer [2].…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations